2019
DOI: 10.1371/journal.pone.0213293
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of weather, soil and plant microbial communities in rapid decline of apple trees

Abstract: An unusual decline and collapse of young established trees known as "rapid apple decline" (RAD) has become a major concern for apple growers, particularly in the northeastern United States. This decline is characterized by stunted growth, pale yellow to reddish leaves, and tree collapse within weeks after onset of symptoms. We studied declining apple trees to identify potential involvement of abiotic and biotic stresses. We used 16S and ITS to profile bacterial and fungal communities in the soil, rhizosphere, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 44 publications
(64 reference statements)
1
41
0
Order By: Relevance
“…Such correlation between δ 13 C and precipitation has also been demonstrated in other studies [33][34][35], suggesting higher stomatal conductance in moister environments. Similar confluent and sequential stresses were also reported as potential causes for the decline of Atlas cedar [36] and cultivated apple trees showing symptoms of "rapid apple decline" in North America [37]. Our study also implies that pest infestation aggravated the decline in WUE, especially in drought conditions.…”
Section: Confluent Impacts Of Pest Infestation and Droughtsupporting
confidence: 85%
“…Such correlation between δ 13 C and precipitation has also been demonstrated in other studies [33][34][35], suggesting higher stomatal conductance in moister environments. Similar confluent and sequential stresses were also reported as potential causes for the decline of Atlas cedar [36] and cultivated apple trees showing symptoms of "rapid apple decline" in North America [37]. Our study also implies that pest infestation aggravated the decline in WUE, especially in drought conditions.…”
Section: Confluent Impacts Of Pest Infestation and Droughtsupporting
confidence: 85%
“…The cause of apple decline has remained elusive in both the eastern United States and in Washington state. A study by Singh et al [4] ruled out the involvement of ASGV, ASPV, and ACLSV, while in this study we have found several more known viruses that require investigation. But what else?…”
Section: Novel Apple Virusesmentioning
confidence: 57%
“…At this point there is no common thread distinguishing declining trees from healthy trees. A recent examination of a variety of factors, including weather, soil chemistry, viral infection, and microbial communities was conducted and no obvious difference was observed between symptomatic and asymptomatic trees [4]. This suggests that some other, as yet unidentified factor, is ultimately responsible for decline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations